1994
DOI: 10.1007/bf00132539
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear DNA content of Pinus sylvestris (L.) as determined by laser flow cytometry

Abstract: Nuclear DNA content was determined in nuclei isolated from needles, stems and roots of in vitro grown seedlings and from megagametophytes and embryo of mature seeds in three accessions of Pinus sylvestris L. One accession was from Inari, northern Finland at timber line, and two accessions were from the Alpine region in Italy. Nuclei were mechanically isolated by a chopping method, stained with propidium iodide, and DNA content was determined using an EPICS PROFILE laser flow cytometer. Nuclei isolated from lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
2
1

Year Published

1997
1997
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 29 publications
0
13
2
1
Order By: Relevance
“…On the contrary, Hall et al (2000) detected variations in some tropical hard pines. Valkonen et al (1994) also showed some individual variations in Pinus sylvestris in different tissues, which would suggest a methodological source of variation.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…On the contrary, Hall et al (2000) detected variations in some tropical hard pines. Valkonen et al (1994) also showed some individual variations in Pinus sylvestris in different tissues, which would suggest a methodological source of variation.…”
Section: Introductionmentioning
confidence: 91%
“…and other gymnosperms have been mostly obtained by flow cytometry Wakamiya et al 1993;Valkonen et al 1994;O'Brien et al 1996;Murray 1998;Bou Dagher-Kharrat et al 2001;Siljak-Yakovlev et al 2002). Estimates obtained using this method have not shown such large discrepancies among populations for the same species and seem to be more accurate and reliable.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…All leaf samples (Ϸ50 mg each) were collected from the three-leaf stage. Protoplasts were isolated as before (34), then resuspended in 1 ml of nuclear buffer {30 mM sodium citrate, pH 7.0͞45 mM MgCl 2 ͞20 mM Mops [3(N-morpholino)propanesulfonic acid]͞1% (wt/vol) Triton X-100͞5 l(ml) Ϫ1 ␤-mercaptoethanol} (35,36), to which 20 m(ml)…”
mentioning
confidence: 99%
“…Recently employed techniques of fluorescent in situ hybridization (FISH) revealed organization of ribosomal genes in Pinus species [9,26,28,34]. Last decade was particularly marked by genome size investigations of Pinus species [2,20,29,39,40,48,50]. All these methods are very useful for consideration of phylogenetic and systematic relationships among pine species.…”
Section: Introductionmentioning
confidence: 99%